2015
DOI: 10.18632/oncotarget.5904
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant rabies virus expressing dog GM-CSF is an efficacious oral rabies vaccine for dogs

Abstract: Developing efficacious oral rabies vaccines is an important step to increaseimmunization coverage for stray dogs, which are not accessible for parenteral vaccination. Our previous studies have demonstrated that recombinant rabies virus (RABV) expressing cytokines/chemokines induces robust protective immune responses after oral immunization in mice by recruiting and activating dendritic cells (DCs) and B cells. To develop an effective oral rabies vaccine for dogs, a recombinant attenuated RABV expressing dog GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Following this rationale, the rRABV expressing GM-CSF (LBNSE-GM-CSF) developed in our previous studies demonstrated the capacity to upregulate DC and B-cell activation both in vitro and in vivo, resulting in enhanced humoral immune responses and protection against rabies in both murine and canine models (10,13,14). Compared with LBNSE-GM-CSF, the rRABV expressing CXCL13 (LBNSE-CXCL13) developed in this study does not promote the activation of DCs in RABV-immunized mice.…”
Section: Discussionmentioning
confidence: 99%
“…Following this rationale, the rRABV expressing GM-CSF (LBNSE-GM-CSF) developed in our previous studies demonstrated the capacity to upregulate DC and B-cell activation both in vitro and in vivo, resulting in enhanced humoral immune responses and protection against rabies in both murine and canine models (10,13,14). Compared with LBNSE-GM-CSF, the rRABV expressing CXCL13 (LBNSE-CXCL13) developed in this study does not promote the activation of DCs in RABV-immunized mice.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of MPLA to modulate immune responses has been well studied before [20,32]. Activation of dendritic cells (DC) was reported to contribute to humoral immune responses induced by live rabies vaccine [19,31,33]. In order to evaluate the ability of MPLA to activate DCs in vitro, bone marrow-derived dendritic cells (BMDC) from wild type (WT) mice and TLR4 knock-out (TLR4 −/− ) mice were cultured for 6 days, and then harvested with the above-mentioned method.…”
Section: Mpla Facilitates the Maturation Of Bmdc Via A Tlr4-dependentmentioning
confidence: 99%
“…However, in China, as well as lacking an oral vaccine for the control of rabies in stray dogs and wild animals, no veterinary rabies vaccine has so far been developed or imported for domestic animals except owned dogs [6,7]. Although rabies prophylactic vaccination has been recommended for cattle by the World Organization for Animal Health (OIE), and successfully performed in rabies endemic countries [8], it is uncertain that emergency immunization using local canine rabies vaccine products has been able to block the spread of infection in ruminants.…”
Section: Introductionmentioning
confidence: 99%